Optimisation of performance through kinematic analysis of the different phases of the 100 metres - Mackala, K. (New Studies in Athletics, 2007)
The aim of this study was to investigate the variability of stride length and stride frequency between athletes of different performance levels in the 100m and then verify the influence of these kinematic parameters on the phases of the race and technical efficiency. Data from a group of 8 average male sprinters (mean performance 11.18) and the men`s 100m finalists in 1991 IAAF World Championships in Athletics were compared. Based on statistical analysis of the kinematic parameters, the author identifies different phase structures for the races of the two groups. The results suggest that stride length contributes much more to the course of the 100m than stride frequency, which cannot anymore be considered the most important performance-determining factor in either average- or high- level performers. It is therefore necessary to find an optimal balance between stride length and stride frequency, especially during the initial acceleration phase, in order to optimise the performance.